Bioelectrical Brain Activity in Schizophrenic Female Patients with Auditory Verbal Hallucinations - Daria A. Leonovich; Olga V. Shevaldova; Alexandr V. Vartanov; Maria D. Krysko; Valeria I. Zakurazhnaya; Alexandra G. Ochneva (Вестник Кемеровского государственного университета. Серия: гуманитарные и общественные науки)
Schizophrenia affects 0.45% of adult population, which is a serious burden for healthcare and social security. It deteriorates the quality of life of patients and their families. Auditory verbal hallucinations prevent schizophrenic patients from professional activities and social interactions. Given that schizophrenic symptoms are gender-specific, the present study focused exclusively on female patients. Understanding the functional characteristics of inner speech in women with schizophrenia has important clinical implications. A deeper comprehension of these neural mechanisms may help to select targeted neuromodulation, pharmacotherapy, and psychotherapy to alleviate the stress and consequences of auditory verbal hallucinations, which share similar psychophysiological mechanisms with inner speech. Auditory verbal hallucinations are a research field that evolves based on qualitative interdisciplinary approaches. These approaches consider both contextual and subjective aspects, as well as their correlations with more general alterations in brain structure and self-perception issues in schizophrenic patients. The research objective was to determine the functional differences during silent pronunciation of stimulus words between female schizophrenic patients with a history of auditory verbal hallucinations and women without mental disorders. The analysis of brain bioelectrical activity patterns relied on a novel method of virtually implanted electrode (Russian Federation Patent No. 2785268). It included two cohorts: control group (22 women, 21–66 y.o., mean = 41.9, SD = 16.1) vs. schizophrenic patients of the Alekseev Psychiatric Clinical Hospital No. 1, Moscow (22 women, 23–65 y.o., mean = 41.8, SD = 10.4). The patients were receiving similar pharmacological therapy (17 cases of F20, 3 cases of F23). The stimuli included Russian words sakhar (sugar), shashlyk (barbecue), and raketa (rocket). One instance of raketa was pronounced by a speaker with speech impairments. The participants received the stimuli through headphones in random order while keeping their eyes closed. The study revealed significant differences between women with schizophrenia and the control group: low ERP amplitude in the left Wernicke area (latency 180–210 ms), activation peak delayed by 150 ms in the right Wernicke area, bilateral supramarginal gyrus and left cerebellar region, as well as significant changes in the ventral striatum activity at 180–330 ms.